PERANAN GURU PENDIDIKAN AGAMA ISLAM TERHADAP PENINGKATAN MUTU PENDIDIKAN AGAMA ISLAM DI SD AL-QUR’AN DARUL ISHLAH BANJAR MARGO TULANG BAWANG - Yana, Eli; Giman Bagus Pangeran; Nur Azizah (STKIP Subang, 2025)
One of the most important and crucial elements in improving the quality of Islamic religious education is the role of Islamic religious education teachers. Students' morals, religious knowledge, and the application of all Islamic teachings in their daily lives are the duties and roles that Islamic religious education teachers must fulfill. This refers to the efforts of Islamic religious education teachers in creating and planning programs, implementing and evaluating religious activities, and producing a generation that is qualified in both material and practice, while continuously improving the quality of Islamic religious education. This study aims to (1) describe the role and efforts made by Islamic religious education teachers to improve the quality of Islamic religious education at Al-Qur'an Darul Ishlah Elementary School, and (2) describe the obstacles experienced by Islamic religious education teachers in improving the quality of Islamic religious education at Al-Qur'an Darul Ishlah Elementary School. This research, conducted at Al-Qur'an Darul Ishlah Elementary School, used qualitative research methods and was descriptive qualitative.The collected data were generated through observation, interviews, and documentation. The results of the research that has been conducted are, (1) the role of Islamic religious education teachers in improving the quality of Islamic religious education at Al-Qur'an Darul Ishlah Elementary School is by organizing, implementing and evaluating religious activity programs so that students can understand and apply them in everyday life. These religious activities include emphasizing moral learning, Dhuha prayer, Friday infaq activities, the flagship program of memorizing the 30 juz of the Qur'an and memorizing important surahs such as Surah Yaseen with the insertion of learning to read the Qur'an using the Yanbu'a method. (2) the obstacles for Islamic religious education teachers in improving the quality of Islamic religious education are the lack of support and concern from parents, lack of facilities and infrastructure, lack of enthusiasm from teachers and these obstacles come from the students themselves who are less disciplined in teaching and learning activities.